Prevalence of pks gene cluster and characteristics of Klebsiella pneumoniae‐induced bloodstream infections - Lan, You (J Clin Lab Anal, 2019)
BACKGROUND: The emerging pks‐positive (pks(+)) strains have aroused great public concern recently. Colibactin, encoded by pks gene cluster, has been reported to be involved in DNA damage and increased virulence. Little is known about its prevalence among Klebsiella pneumoniae‐induced bloodstream infections (BSIs). Therefore, the aim of this study was to investigate the prevalence of pks gene cluster, and molecular and clinical characteristics of K pneumoniae‐induced BSIs. METHODS: A total of 190 non‐duplicate K pneumoniae bloodstream isolates were collected at a university hospital in China from March 2016 to March 2018. Molecular characteristics including capsular types, virulence, and pks genes were detected by polymerase chain reaction (PCR). Clinical characteristics and antimicrobial susceptibility were also investigated. RESULTS: Overall, 21.6% (41/190) of K pneumoniae bloodstream isolates were hypervirulent K pneumoniae(hvKP). The prevalence of pks gene cluster was 26.8% (51/190). The positive rates of K1, K57, and genes associated with hypervirulence, that is, rmpA, wcaG, mrkD, allS, ybtS, kfu,and iucA, were significantly higher in the pks(+)isolates than the pks‐negative (pks (−)) isolates (P < 0.05), while the pks(+) isolates were significantly less resistant to 11 antimicrobial agents than the pks (−) isolates. Multivariate analysis showed diabetes mellitus, and K1 and K20 capsular types as independent risk factors for pks (+) K pneumoniaebloodstream infections. CONCLUSIONS: The pks (+) K pneumoniae was prevalent in individuals with bloodstream infections in mainland China. The high rates of hypervirulent determinants among pks (+) K pneumoniaerevealed the potential pathogenicity of this emerging gene cluster. Diabetes mellitus, and K1 and K20 capsular types were identified as independent risk factors associated with pks(+) K pneumoniaebloodstream infections. This study highlights the significance of clinical awareness and epidemic surveillance of pks(+)strains.